Variability of wind stress and currents at selected locations over the north Indian Ocean during 1977 and 1979 summer monsoon seasons (MAUSAM, 1988)
Intra-seasor1al variability of wind stress, wind stress curl and currents at different locations over the northern Indian Ocean during two contrasting monsoon seasons has been investigated making use of  the time serifs data collected during MONSOON-77 and MONEX-79. In general, the surface wind stress and near surface current fields are strong during a good monsoon year (1977) as compared to those in a bad monsoon year (1979) under similar synoptic conditions together with the prevalence of high and low Intensities during active/pre-onset and break phases respectively the wind stress curl is found to be more negative and stronger in the Arabian Sea In active phase whereas It IS closer to zero during break monsoon conditions In the Bay of Bengal. A better association exists between wind stress and near surface currents in the Arabian Sea than in the Bay of Bengal.